Cleaning the Air of Tehran, One Bus at a Time : Retrofit Solutions for the Ageing Diesel Bus Fleet in Tehran - World Bank (World Bank, Washington, DC, 2019)
According to a report by the World Bank published in April 2018, air pollution in Tehran incurs annual loss of billions of dollars and over 4,000 premature deaths from exposure to fine particles ambient concentrations. Particulate matter (PM), one of the primary pollutants from diesel exhaust, is associated with many different types of respiratory and cardiovascular effects, and premature mortality. The main objective of this study is to evaluate the cost effectiveness of retrofitting existing city diesel bus fleet in Tehran with best available Diesel particulate filters (DPFs) available in the market. The report provides an updated assessment on the diesel retrofit solutions for an ageing diesel city bus fleet in Tehran based on publicly available information. The economic benefits of DPF installed in buses are evaluated with standard techniques of environmental economics, and technological assumptions about how much PM emissions can be avoided and control costs. The report highlights a number of national, regional and local examples of effective emission control program that exhibit best practices from around the world. Also, it presents important features and global experiences of successful retrofit program on heavy-duty diesel vehicles (HDDVs), including benefit-cost analysis from several case studies to help Tehran city leadership in taking informed economic and policy decisions. Finally, it recommends a set of critical actions to the government both at the national and local level for implementation of an effective emission control programs.